2019
DOI: 10.3390/ijerph16101671
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Concept for a Walker with a Self-Locking Mechanism Using a Single Mechanical Approach

Abstract: Background: The ageing process involves a natural degeneration of physiological function and can imply life constraints, namely during activities of daily life (ADL). Walking can be strongly affected by strength, gait, and balance changes, which affect quality of life. The quality of life of the older adult is associated with available solutions that contribute to an active and safe ageing process. Most of these solutions involve technical aids that should be adapted to older adults’ conditions. Aim: To identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…A primary purpose of a standard walker is partial weight bearing of the user [37]. It was observed that the people with osteoporosis put more force on the walker while walking, in comparison to the people without osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…A primary purpose of a standard walker is partial weight bearing of the user [37]. It was observed that the people with osteoporosis put more force on the walker while walking, in comparison to the people without osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…For examples, a passive walker is powered by the user-supplied forces with controlled brakes [ 8 , 9 , 10 ]. Recently, the walker powered by motors to steer the walker has attracted a lot of attention [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Patel et al [ 11 ] used an active walker as the experimental platform to exploit the interactions between an intelligent mobility aid and the human operator.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al [ 17 ] proposed a walking assist robot which can detect the abnormal gait pattern in users for fall prevention. Lopes et al [ 18 ] presented an innovative research, in which whenever a certain pressure is exerted, the walker gets slower to avoid the occurrence of falls by blocking the wheels. Kapsalyamov et al [ 23 ] proposed a wearable robotic solution to assist the elderly for mobility.…”
Section: Introductionmentioning
confidence: 99%